THE IMPACT OF MONETARY AND NON-MONETARY INCENTIVES ON EMPLOYEES’ MOTIVATION IN PT XYZ’S FINANCE FUNCTION IN SURABAYA - Richard Gunawan; Hendry Febrianto (iBuss Management, 2014)
While successful corporate strategies are those executed well by the management, the execution itself will depend on the employees involved in the business process. Thus, it is very important for the management to understand the factors that influence employees to be motivated in performing the required tasks and achieve or even surpass the management expectation.PT XYZ’s strong performance amid the fierce competition in the industry makes the company cannot afford to ignore the contribution of their people to strive. Considering which incentives utilized by PT XYZ that affect employees’ motivation the most will help PT XYZ to manage its employees more effectively. This research was conducted in PT XYZ’s Finance function in Surabaya by distributing questionnaires to 102 employees. The sampling method used was simple random sampling. The data were analyzed using Multiple Linear Regression Analysis. The results show that monetary incentives, tangible non-monetary incentives, and intangible non-monetary incentives have significant impact on employees’ motivation. When analyzed individually, tangible non-monetary incentives are the only factors having no significant impact on employees’ motivation. In addition, the result indicates that intangible non-monetary incentives are the most influential factors affecting employees’ motivation in PT XYZ’s Finance function. Keywords: Human Resource, Motivation, Employees’ Motivation, Incentives, Monetary Incentives, Non-monetary Incentives.